The Influence of Transformational Leadership on Employee Performance at PT. Honda Tugu Mandiri - Sulistiyo, Jimmer (Blantika: Multidisciplinary Journal, 2025)
This study aims to analyze the influence of transformational leadership on employee performance at PT. Honda Tugu Mandiri. Transformational leadership is expected to improve employee motivation, engagement, and performance within the company. The research uses a descriptive quantitative approach with a survey method to collect data. Data were gathered through questionnaires distributed to 100 employees of PT. Honda Tugu Mandiri. The results indicate that there is a significant positive relationship between transformational leadership and employee performance, measured through increased productivity, quality of work, and job satisfaction. This study provides insights into the importance of implementing transformational leadership to enhance employee performance.